Sex-chromosome Variability in Zygodontomys lasiurus (Rodentia, Cricetidae) - Kasahara, Sanae [UNESP] (1983)
Cytogenetic studies were performed on 26 specimens of the rodent Zygodontomys lasiurus (2n=34, 2n=33/34), collected in the State of São Paulo, Brazil. The G- and C-band patterns of mitotic chromosomes were studied and the NORs were localized in the karyotype. Two types of acrocentric X chromosomes, morphologically distinctive, were observed, one of them having an enlarged short arm (Xm). In some females the sex chromosome pair consisted of an Xm and a small submetacentric Xd similar to the Y chromosome. The possibilities that these are females bearing a deletion in one X plus a duplication in the other, or are true XY females are discussed. A chromosome mosaicism of 2n=33/34 type was detected in one female. The 2n=34 cell line had an XmX constitution, while the 2n=33 cells were XmO. Both early dissociation between X and Y chromosomes and altered segregation of such chromosomes at metaphase II were observed in one male specimen. © 1983, Japan Mendel Society, International Society of Cytology. All rights reserved.